SYSTEMATIC LITERATURE REVIEW METODE PRISMA: STRATEGI GURU DALAM MENGHADAPI DINAMIKA PERUBAHAN BUDAYA - Kurniawan, Hardika Nifail; Atmojo, Pengkuh Aji; Wasino; Aricindy, Argitha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The flow of globalization, accompanied by accelerated digitalization, creates multi-layered challenges for basic education, especially in character formation and maintaining students' cultural identity. It is not enough for elementary school teachers to only carry out the function of transferring knowledge; they are required to respond to cultural shifts through contextual and adaptive learning designs. This research aims to systematically map elementary school teachers' strategies in responding to the dynamics of cultural change. The study used a qualitative approach with the Systematic Literature Review (SLR) method within the PRISMA framework, through the stages of identification, screening, feasibility assessment, and synthesis of 12 scientific articles that met the inclusion criteria. The results of the study reveal four dominant strategies: integrating local wisdom values ​​in learning, strengthening school culture with an identity, implementing the Culturally Responsive Pedagogy (CRP) and Culturally Responsive Teaching (CRT) frameworks, and utilizing digital media based on local cultural riches. These four strategies have been proven to contribute to forming character, affirming cultural identity, increasing learning engagement, and fostering a tolerant attitude towards diversity. This study concludes that the dynamics of cultural change due to globalization should not only be seen as a threat, but also as a momentum for teachers to provide learning that is meaningful, inclusive, and remains rooted in local cultural values.